Educational Technology in Improving Quality of Engineering Education - Kulkarni, P. D. (Journal of Engineering Education Transformations, 2000)
The paper emphasizes that in order to plan educational development in 'Engineering Education', the planner must view the educational system as operating at five levels. For educational development to occur the system should change at all these levels&should be manned by educational professionals. Professionals in education draw their expertise from educational sciences&educational technology disciplines. There are various categories of educational professionals, but all of them should have a solid base in the foundational disciplines of Educational Technology. Here ET is defined as Technology of Education; use of scientific concepts, principles&techniques for improving educational practice. Attempt has been made to describe key concepts. Educational authorities should identify specific strategies at all levels to be able to change system. All strategies should aim at developing collective consciousness of the importance of Educational Technology to bring about change in orientation, Lastly, list of projects is made.